Relationships between financial stress, adult attachment, religiosity, marital communication and marital quality among Malay Muslim newly-weds in the Klang Valley, Malaysia - Sahrani, Syah Qurratu 'Aini (2016)
Various research had highlighted that marital quality are going downward trajectories and early years of marriage has been highlighted as the most crucial stage in marriage life. For years, factors influencing marital quality has always been the basic interest among family researchers and academicians and they have listed out various factors that may influence marital quality. Nevertheless, less research has focused on the combination of financial stress, adult attachment, religiosity and marital communication in predicting marital quality among Muslim newlyweds. Thus, guided by Vulnerability Stress Adaptation Model (VSA) this current study aims to examine the role of marital communication as mediator for the relationships between financial stress, adult attachment, religiosity and marital quality. Data were gathered from 549 Muslim who were married less than 2 years at the time of data collection . This study was part of the Exploratory Research Grant Scheme (ERGS) research entitled “Exploring Marital Quality in the First Year of Married Life: Risk and Protective Factors for Marital Instability” funded by Ministry of Education. This research utilized correlational research design and sample of the study were recruited using convenience and snowball sampling technique. Data were collected using five validated and reliable instruments to measure financial stress, adult attachment, religiosity, marital communication and marial quality. Instruments used in this study were InCharge Financial Distress/Financial Well-Being Scale, Adult Attachment Scale, Intrinsic Religious Motivation Scale, Dyadic Adjustment Scale, and The Three Couple Scale PREPARED/ENRICH: Marital Satisfaction, Communication and Conflict Resolution. All instruments were translated into Malay and data were analyzed using descriptive, bivariate and multivariate analyses. Results of Pearson correlations showed that income, educational backgroud, financial stress, adult attachment, religiosity and marital communication were significantly related with marital quality among Muslim newly-weds in Klang Valley. Series of multiple regression analyses conducted in this study highlighted that marital communication mediates the relationship between attachment avoidant, attachment anxiety, religiosity and marital quality. However, the mediation analysis between financial stress and marital quality was not statistically significant. Finally, multiples regression analysis was conducted to predict the most significant predictors for marital quality. Financial stress were found to be the most significant indicators to predict marital quality among Muslim newly-weds in Klang Valley. It is predicted that couples that encounter financial stress will have lower marital quality if the problem was not tackled in the earlier phase of marriage. Based on this study, it is recommended that future interventions and research should focus more on financial stress and marital communication in studying marital quality among newly-weds.